A Review Study on Macrolides Isolated from Cyanobacteria - Wang, Mengchuan (Mar Drugs, 2017)
Cyanobacteria are rich sources of structurally-diverse molecules with promising pharmacological activities. Marine cyanobacteria have been proven to be true producers of some significant bioactive metabolites from marine invertebrates. Macrolides are a class of bioactive compounds isolated from marine organisms, including marine microorganisms in particular. The structural characteristics of macrolides from cyanobacteria mainly manifest in the diversity of carbon skeletons, complexes of chlorinated thiazole-containing molecules and complex spatial configuration. In the present work, we systematically reviewed the structures and pharmacological activities of macrolides from cyanobacteria. Our data would help establish an effective support system for the discovery and development of cyanobacterium-derived macrolides.